Some Impacts of Overgrazing by Reindeer in Finnmark, Norway - Evans, Robert (Rangifer, 1996)
Some impacts of reindeer grazing on Finnmark's landscape are briefly described. Information on the impacts was gathered mostly by surveying 17 sample transects in the field, often 90 m in length; as well as by examining other localities in Finnmark, particularly the area around Ifjordfjellet. The results of the surveys along fences as well as in the open countryside are given. These show that much degradation has taken place along fences and that adjacent to the fence more than half the soil can be exposed to trampling and the weather. At Ifjordfjellet damage along 22.4 km of fence separating summer grazings from spring and winter grazings was severe or very severe (> 30% bare soil exposed) over 39% of its distance. Land alongside an 8.0 km long fence built to aid management of the reindeer herds in summer was even more degraded, with 56% of its length on the 'inner' side severely or worse damaged, and 70% on the 'outer' side. In open landscapes erosion by tracking, trampling and the weather is most likely in wet peaty hollows; on slopes steeper than 7 degrees where soils are peaty or 13 degrees where they are mineral-based; at the edge of terrace landforms or where drumlins occur; and especially where deep sandy soils occur in eskers or other fluvioglacial land-forms. Soil is being denuded at rates of 1-3 mm per year. Evidence for reindeer grazing is widespread throughout Finnmark: from the almost ubiquitious presence of dung; to the disappearance of lichens by trampling in summer grazings and by overgrazing in winter grazings; to the presence of bare soil in many localities. Where reindeer grazing is confined either by fences or topography, degradational thresholds are lowered so that, for instance, peaty and mineral soils begin to erode on slopes as low as 4 degrees. This degradation has mostly come about in the last two or three decades as reindeer numbers have increased markedly, often by a factor of 2 or 3.